The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1759-5436.2011.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining Development in the UK? Findings from the UK Public Opinion Monitor

Abstract: The UK Public Opinion Monitor (UKPOM) provides a unique opportunity to explore changes in attitudes of the UK public over time. This article presents findings from the UKPOM on how people in the UK have experienced the financial crisis and how, if at all, this has caused them to think differently about aid and development. We find that respondents had been affected by the economic crisis and were worried about the impact on their own finances and the UK economy. Although respondents had a feeling of interconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Research also found that support for general cuts in social spending is relatively low, while there is more support for specific cuts (Roller, 1999). Likewise, support for spending on development aid decreases in times of cuts and is replaced by local and domestic priorities (Lindstrom and Henson, 2011). In the literature on welfare spending, the self-interest argument states that those respondents who are (potential) beneficiaries of welfare-related services are more likely to have positive attitudes towards the welfare state and related concepts when compared to those who are 'better off'.…”
Section: The Government Is Wasting Our Money: the Role Of Political Disaffectionmentioning
confidence: 98%
“…Research also found that support for general cuts in social spending is relatively low, while there is more support for specific cuts (Roller, 1999). Likewise, support for spending on development aid decreases in times of cuts and is replaced by local and domestic priorities (Lindstrom and Henson, 2011). In the literature on welfare spending, the self-interest argument states that those respondents who are (potential) beneficiaries of welfare-related services are more likely to have positive attitudes towards the welfare state and related concepts when compared to those who are 'better off'.…”
Section: The Government Is Wasting Our Money: the Role Of Political Disaffectionmentioning
confidence: 98%
“…Unsurprisingly, public attitude towards international development organisations is sceptical. People are doubtful about the effectiveness of international development organisations and the efficiency with respect to how their money is spent (Bekkers and Boonstoppel, 2011;Carabain et al, 2012;Council on Foreign Relations, 2012;European Commission, 2010;Gijsbers and van der Lelij, 2010;Hento, 2011;Lindstrom and Henson, 2011;Pollet, 2012;PQR, 2010;Ravelli and Verhoeven, 2008). People are sceptical about the achievability of poverty reduction and pose critical questions on the share of the budget that international development organisations spend on overhead costs (PQR, 2010).…”
Section: Introductionmentioning
confidence: 99%